Synthesis of Ni/Al2O3 and Ni–Co/Al2O3 coatings onto AISI 314 foams and their catalytic application for the oxidative dehydrogenation of ethane - Bortolozzi, Juan Pablo (2013)
The aim of this work was to obtain alumina-supported Ni and Ni–Co oxide catalytic coating onto an AISI 314 foam (60 ppi) so as to produce a good distribution of the catalytic components and reproduce characteristics of their interactions similar to those observed in the powder catalysts. These catalytic systems were characterized by different techniques (Laser Raman spectroscopy, X-ray diffraction, temperature-programmed reduction, scanning electron microscopy and energy-dispersive X-ray analysis). The oxidative dehydrogenation of ethane was used as test reaction. The results indicated that the Ni and Ni–Co/Al2O3 powder catalysts were active and selective for this reaction. For the active metal loading used (15 wt%), the addition of cobalt with an atomic ratio of Co/Ni = 0.114 slightly improved the ethylene productivity, possibly due to the enhancement of Ni dispersion. However, the addition of a higher amount (Co/Ni = 0.253) led to a lower productivity, probably due to the presence of cobalt compounds and to the increase in the NiO crystal size. The structured systems showed a performance similar to that of the corresponding powder forms and they also showed good adhesion of the catalytic layer onto the metallic foams. The features of the resulting structured systems are very sensitive to the variables which involve the deposition method. Therefore, it is necessary to take into account the control of such parameters in order to obtain good, repetitive depositions of the active components and a correct distribution of the support in the coverage. In the same sense, the achievement of a constant relationship between the active metals is significant because, otherwise, the activity and selectivity of these systems could be affected.